Peran Guru Pendidikan Agama Islam dalam Meningkatkan Akhlak Siswa di SMP Negeri 2 Rangsang Pesisir - Miftahul Shulha Badriyah; Yudi Irwan (Jurnal Pendidikan Islam Indonesia, 2026)
This research is motivated by the important role of Islamic Religious Education teachers in developing students' morals amidst technological developments and increasingly complex social environments. This study aims to determine the role of Islamic Religious Education teachers in developing students' morals and to identify supporting and inhibiting factors in the process of developing students' morals at SMP Negeri 2 Rangsang Pesisir. This study used a qualitative approach with a descriptive approach. Data collection techniques included observation, interviews, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results indicate that Islamic Religious Education teachers act as educators, guides, motivators, role models, and supervisors in developing students' morals through learning, role models, advice, and religious activities at school. Supporting factors in this research include school support, cooperation between teachers and parents, and school religious activities. Obstacles encountered include the influence of social media, the social environment, and a lack of attention from some parents to developing students' morals.